Analysis of Physical Activity, Motor Skills, and Social Skills in Children with Disabilities with Autism Spectrum Disorder (ASD) - Tenica Meliana Saputri; Jajat; Kuston Sultoni (Universitas Negeri Semarang, 2025)
This study aims to analyze physical activity, gross motor skills, and social skills in children with Autism Spectrum Disorder (ASD) and to examine the relationship between these three variables. This study used a descriptive quantitative method involving nine children with ASD at SLB-D YPAC Bandung. Physical activity was measured using ActiGraph GT3X for seven days, motor skills were assessed through long jump, ball throw, 10-meter run, and balance tests, while social skills were measured using the Social Skills Questionnaire (SSQ). Data were analyzed descriptively and using Spearman's correlation to examine the relationship between variables. The results showed that the level of physical activity among children with ASD tended to be low, gross motor skills varied between individuals, and social skills were in the moderate category. Correlation analysis showed no strong relationship between physical activity, motor skills, and social skills, reflecting the diversity of developmental characteristics in children with ASD. However, these three aspects remain important to improve through structured interventions tailored to individual needs. These findings emphasize the importance of a holistic approach in supporting the physical, motor, and social development of children with ASD.